Effect of temperature and substrate on the germination of Apuleia leiocarpa (Vogel) J.F. Macbr (amarelão) seeds - José, Anderson Cleiton; Coutinho, Adriano Barros; Erasmo, Eduardo Andrea Lemus (Agrarian, 2011)
<span style="line-height: 115%; font-family: ";Times New Roman";; font-size: 11pt; mso-fareast-font-family: 'Times New Roman'; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">This work aimed to evaluate the effect of different substrates and temperatures on the germination of amarelão (Apuleia leiocarpa) seeds. It was used four types of substrates (between paper, over paper, paper roll and sand) and five temperatures (constant: 20, 25, 30 and 35°C) and alternated (20/30°C). Germination was evaluated daily after imbibition counting seeds with radicle protrusion of at least 2mm. It was calculated the final percentage of germination and the indexes T50 and U7525 to estimate the speed and uniformity of germination, respectively. It was not observed differences in the percentage of final germination between the substrates in the temperatures of 25 and 30°C, However, when seeds were germinated at 30°C in paper roll an increase in speed of germination (reduction of T50) was observed. Germination was not affected in the tested temperatures, except for germination at 35°C, when a reduction in the percentage of final germination was observed. However, despite the lack of effect of temperatures on the percentage of germination for the majority of the tested temperatures, an effect on velocity and uniformity of germination was observed. Higher speed and uniformity were achieved when seeds were incubated at 30°C. In conclusion, paper roll and the temperature of 30°C (constant) are the best conditions for germination of A. leiocarpa seeds, which provide higher percentage of germination, germination velocity and uniformity.